Chapter La città come nodo della rete eco-territoriale della bioregione urbana - Poli, Daniela (Territori, 2023)
The regeneration of metropolitan contexts and large planetary urbanizations can no longer be postponed. The use of more and more refined techniques and technologies using metaphor in nature has become increasingly conspicuous. For there to be a real turnaround, however, concepts such as 'biodiversity', 'biomimicry', and 'ecositemic services' need to find their proper design definition, apt to maintain the complexity of settlement forms together with the complexity of life. From a bioregional point of view, it seems useful to rethink the city as a complex node of the eco-territorial network to substantiate the concept of urban bioregion.